Sintesis Silika Mesopori Menggunakan Bahan Dasar Na2SiO3 yang Dihasilkan dari Pasir Silika dengan Metoda Sol-Gel - Armelia Ananda; Syamsi Aini (Jurnal Periodic Jurusan Kimia UNP, 2021)
The synthesis of natural silica-based mesoporous silica is continuously being carried out, especially to obtain silica with high crystallinity and larger pores from high water absorption. In this study, the synthesis of mesoporous silica using the sol-gel method by adding hexane and varying the mass addition of Pluronic 104 surfactant (2 g, 4 g, 6 g). The synthesized silica was characterized using XRD.. The results of measurements using XRD showed that the diffraction pattern appeared as the relevant peak for the three products with standard mesopore silica diffraction patterns, namely wide and low peaks at 2ϴ 22.7; 21.8; 22.1 for the products SM02, SM04 and SM06 respectively. Meanwhile, the highest intensity / crystallinity given by the SM06 sample.